Awareness Regarding Safe Drinking Water among People Living in Rural Area of Bangladesh - Kabir, Md Humayun; Asgar, Nilufar; Alam, Fakir Sameul; Ansari, Mahmuda (Community Based Medical Journal, 2025)
This cross-sectional, descriptive study was conducted in a rural area of West Bhagalpur village under Bajitpur upazila of Kishoreganj district, Bangladesh, from July 2023 to June 2024, to determine the awareness regarding particular aspects of safe drinking water among the rural adults. A convenient non-probability sampling was adopted. A total of 125 participants were interviewed based on a semi-structured questionnaire. Out of 125 respondents, 44(35.2%) were male and 81(64.8%) were female; all were aged between 18 and 65 years. Regarding qualities for safe drinking water, most of them said 82(65.6%) colorless, odorless, free from turbidity, tasteless and other said 24(19.2%). The majority 103(82.4%) had shallow tube well, 14(11.2%) had deep tube well, 7(5.6%) had tap water, only 1 used pond water. Most of them were taking drinking water without purification direct from tube well 88(70.4%), followed by boiling and filters 16(12.8%) and rest of them purify their drinking water by disinfection 5(4%). For improvement of water supply, most of them recommended 23(46.93%) to provide subsidized filters, create awareness regarding hazards of impure water drinking and built more tube well and followed by built more tube wells 16(32.65%), create awareness 6(12.24%) and provide subsidized filters 4(8.16%). For storage of water most of them used jug 86(68.8%), followed by bucket 25(20%), mud pot 8(6.4%) and only 6(4.8%) used others containers. 121(96.8%) had no water-borne disease in the last 6 months, while 4(3.2%) had diarrhoea. Surprisingly, most of them said yes to store water for future use 84(67.2%), while 41(32.8%) declined. This study presented a comprehensive overview of the awareness regarding particular aspects of safe drinking water among people living in rural areas of Bangladesh. CBMJ 2025 July: vol. 14 no. 02 P:149-153